2016
DOI: 10.1111/fme.12162
|View full text |Cite
|
Sign up to set email alerts
|

Early detection of reproduction deficits and the compensatory potential of enhancement stocking for vendace, Coregonus albula, fisheries in German lakes

Abstract: Enhancement stocking is a widespread but rarely evaluated practice in German vendace, Coregonus albula L. fisheries, which is precautionarily carried out to buffer yield fluctuations. However, it is assumed that stocking of larval vendace can elevate year‐class strength only in the presence of substantial reproductive deficits, which so far cannot be detected prior to the spring time period when stocking is conducted by fisheries managers. Simple measures for the early quantification of natural reproduction we… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
9
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(10 citation statements)
references
References 27 publications
1
9
0
Order By: Relevance
“…A relatively low proportion of stocked whitefish of one cohort, as we found for Lake Constance with 17.4% for the 2016 cohort and 24.5% for the 2018 cohort, has also been reported for other lakes in the alpine region (Meng et al, 1986;Müller, 1990) and elsewhere (Salojärvi, 1992;Wanke et al, 2016). Most of the time, natural recruitment occurred in those lakes and several authors argue that stocking is superfluous under these conditions (Gerdeaux, 2004) or that stocked fish only survive in high numbers if natural recruitment is deficient (Wanke et al, 2016;Wedekind et al, 2022). Based on these results and the fact that natural born offspring seem to dominate the whitefish cohorts in Lake Constance, higher proportions of stocked fish in the future are unexpected.…”
Section: Proportion Of Stocked Fish In One Cohortsupporting
confidence: 85%
See 3 more Smart Citations
“…A relatively low proportion of stocked whitefish of one cohort, as we found for Lake Constance with 17.4% for the 2016 cohort and 24.5% for the 2018 cohort, has also been reported for other lakes in the alpine region (Meng et al, 1986;Müller, 1990) and elsewhere (Salojärvi, 1992;Wanke et al, 2016). Most of the time, natural recruitment occurred in those lakes and several authors argue that stocking is superfluous under these conditions (Gerdeaux, 2004) or that stocked fish only survive in high numbers if natural recruitment is deficient (Wanke et al, 2016;Wedekind et al, 2022). Based on these results and the fact that natural born offspring seem to dominate the whitefish cohorts in Lake Constance, higher proportions of stocked fish in the future are unexpected.…”
Section: Proportion Of Stocked Fish In One Cohortsupporting
confidence: 85%
“…Meanwhile, other studies have shown that additive effects of stocking with larval fish are generally unlikely, because early life stages are vulnerable to density‐dependent mortality bottlenecks (Beddington et al, 2005; Lorenzen, 2000; Lorenzen & Camp, 2019). In general, additive effects of stocking are only achievable where natural reproduction is severely limited (Beddington et al, 2005; Hühn et al, 2014; Wanke et al, 2016). In ULC, natural reproduction is most likely several times higher than stocking (Baer, Gugele, et al, 2021).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Northern Europeans have a long history of rearing coregonines, such as Vendace C. albula ("European cisco") and European Whitefish C. lavaretus, to advanced life stages on a large scale (e.g., Salonen et al 1996;Wanke et al 2016), methods of which are being implemented in the Great Lakes. Bloaters from Lake Michigan and Ciscoes from remnant Lake Ontario populations have been reared and stocked in Lake Ontario since 2012 (OMNRF 2016;Bronte et al 2017), although the Cisco stocking program was recently discontinued.…”
Section: Introductionmentioning
confidence: 99%